2022
DOI: 10.1038/s41598-022-15504-z
|View full text |Cite
|
Sign up to set email alerts
|

Meeting 24-h movement guidelines and markers of adiposity in adults from eight Latin America countries: the ELANS study

Abstract: This study aimed to compare compliance with 24-h movement guidelines across countries and examine the associations with markers of adiposity in adults from eight Latin American countries. The sample consisted of 2338 adults aged 18–65 years. Moderate-to-vigorous physical activity (MVPA) and sedentary behavior (SB) data were objectively measured using accelerometers. Sleep duration was self-reported using a daily log. Body mass index and waist circumference were assessed as markers of adiposity. Meeting the 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Sedentary behaviour for Japanese fathers in the present study was only similar to the Latin American study [31]. Other percentages were considerably higher in our study.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Sedentary behaviour for Japanese fathers in the present study was only similar to the Latin American study [31]. Other percentages were considerably higher in our study.…”
Section: Discussionsupporting
confidence: 73%
“…Their overall 24-h movement behaviour guideline included meeting MVPA (de ned as ≥ 600 METs minute/week) and sleep (7-9 h/day) recommendations and not having high sitting time (≥ 9 h/day). Ferrari et al [31] reported the prevalence of adults who met the overall recommendations (all 3 behaviours) from eight Latin American countries was 1.6%. With respect to individual movement behaviour recommendations, the proportions meeting each of the recommendations was 58.7% in men and 39.4% in women for physical activity, 21.2% and 22.7% for sedentary behaviour (collected using accelerometers), and 22.8% and 16.5% for sleep time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latin Americans have similar guidelines recommending 150 min a week of moderate activity and < 8 h/d of sedentary behavior. Only 48 and 22% achieved those goals, respectively ( 82 ). The Secretary of Health and Human Services issued a scientific report in 2018 on the vital importance of physical activity.…”
Section: Traditional and Emerging CV Risksmentioning
confidence: 99%
“…Few studies have investigated the acute effect of exercise on people with overweight/obesity, a group that includes the majority of the Colombian adult population, owing to their sedentary behavior and poor health and diet (Ferrari et al, 2022; García et al, 2022). The need for more specific recommendations for at‐risk individuals prompted the present randomized crossover trial, which aimed which.…”
Section: Introductionmentioning
confidence: 99%